Emergent Rainy Winter Warm Spells May Promote Boreal Predator Expansion into the Arctic - Sokolov, Aleksandr A.; Sokolova, Natalya A.; Ims, Rolf A.; Brucker, Ludovic; Ehrich, Dorothee (ARCTIC, 2016)
Climate change has been characterized as the most serious threat to Arctic biodiversity. In addition to gradual changes such as climate warming, extreme weather events, such as melting temperatures in winter and rain on snow, can have profound consequences for ecosystems. Rain-on-snow events lead to the formation of ice layers in the snow pack, which can restrict access to forage plants and cause crashes of herbivore populations. These direct impacts can have cascading effects on other ecosystem components, often mediated by trophic interactions. Here we document how heavy rain in early winter, leading to the formation of a thick layer of ice, was associated with dramatic mortality of domestic reindeer on Yamal Peninsula, Russia. In the subsequent summer, breeding of two boreal generalist predators, red fox and Hooded Crow, was recorded for the first time in a monitoring area in the Low Arctic tundra of this region. We suggest that the resource pulse created by the abnormally high reindeer mortality and abundance of carrion may have facilitated these breeding events north of the known breeding range of the two species. Our observations provide an example of how specific emergent weather events may indirectly pave the way for more abrupt, although possibly temporary, species range changes. Le changement climatique a été caractérisé comme la plus grande menace à la biodiversité de l’Arctique. En plus des changements graduels comme le réchauffement climatique, les phénomènes météorologiques extrêmes comme les températures positives en hiver et la pluie tombant sur la neige peuvent avoir de profondes conséquences sur les écosystèmes. La pluie tombant sur la neige mène à la formation de couches de glace dans le manteau neigeux, ce qui peut avoir pour effet de restreindre l’accès aux plantes fourragères et d’entraîner l’effondrement des populations herbivores. Ces impacts directs peuvent avoir des effets en cascade sur d’autres composantes des écosystèmes, et cette propagation passe souvent par des interactions ...